Object-oriented high level synthesis based on SystemC - Grimpe, E.; Oppenheimer, F. (2001 8th International Conference on Electronics, Circuits and Systems, 2001)
The introduction of object-oriented modelling techniques into the development of hardware seems to open a promising way for mastering the increasing complexity of today's hardware systems. Furthermore it provides the possibility of transferring well known and approved object-oriented modelling techniques from software development to hardware development. Since there is a major difference between the nature of software and the nature of hardware the direct adaptation of common object-oriented programming languages to describing hardware is not possible in general. SystemC is a C++ class library and a methodology that introduces some of the missing typical hardware features in C/C++. This paper describes an extended SystemC based methodology and synthesis techniques allowing the use of object-oriented concepts like classes, polymorphism and inheritance for the description of synthesisable hardware models.